The Implications of QRIS Cross-Border for the Digital Economic Sovereignty of Indonesia in Southeast Asia - Aryowiloto, Julang; Meiliana, Komang Gita; Kelvin, Unegbu Ekene (SIYAR Journal, 2026)
This research aims to investigate the implications of QRIS Cross-Border as a digital payment method for Indonesia's digital economic sovereignty within Southeast Asia. The study specifically analyzes the implementation of QRIS Cross-Border in three countries, namely Thailand, Malaysia, and Singapore, given the significant positive trend evidenced by increasing transaction volumes. Grounded in the concept of economic sovereignty, this study analyzes Indonesia's strategic position within the regional digital economy, its potential to influence the digital economic landscape, and its contributions to the realization of the ASEAN Digital Masterplan 2025. The research employs a qualitative, explanatory approach to examine the relationship between QRIS Cross-Border and Indonesia's digital economic sovereignty in the region. Data for this study were sourced from various channels, including books, journal articles, reports, policy papers, and media publications, in both print and online formats. In conclusion, this study affirms that the implementation of QRIS Cross-Border has significant implications for Indonesia's digital economic sovereignty. Indonesia's strategic position and bargaining power within the regional digital economy have been enhanced. Furthermore, through QRIS Cross-Border, Indonesia is well-positioned to play a crucial role in regional digital economy initiatives and has a significant opportunity to shape the future of Southeast Asia's digital economic landscape.